Severe preschool asthmatics have altered cytokine and anti‐viral responses during exacerbation. Issue 6 (17th May 2020) - Lejeune, Stéphanie; Pichavant, Muriel; Engelmann, Ilka; Béghin, Laurent; Drumez, Elodie; Le Rouzic, Olivier; Dessein, Rodrigue; Rogeau, Stéphanie; Beke, Timothée; Kervoaze, Gwenola; Delvart, Céline; Ducoin, Héloïse; et al.
Abstract: Background: Preschool asthma/recurrent wheeze is a heterogeneous condition. Different clinical phenotypes have been described, including episodic viral wheeze (EVW), severe intermittent wheeze (SIW), and multiple‐trigger wheeze (MTW). Objective: To compare clinical, viral, and inflammatory/immune profiling at exacerbation between MTW, SIW, and EVW phenotypes. Methods: Multicenter, prospective, observational cohort (VIRASTHMA‐2). Children (1‐5 years) with preschool asthma were enrolled during hospitalization for a severe exacerbation. History and anamnestic data, plasma, and nasal samples were collected at exacerbation (T1) and at steady state, 8 weeks later (T2), and sputum samples were collected at T1. Results: A total of 147 children were enrolled, 37 (25%) had SIW, 18 (12.2%) EVW, and 92 (63%) MTW. They were atopic (47%), exposed to mold (22%) and cigarette smoke (50%), and prone to exacerbations (≥2 in the previous year in 70%). At exacerbation, at least one virus was isolated in 94% and rhinovirus in 75%, with no difference between phenotypes. Children with MTW and SIW phenotypes displayed lower plasma concentrations of IFN‐γ ( P = .002), IL‐5 ( P = .020), TNF‐α ( P = .038), IL‐10 ( P = .002), IFN‐β ( P = .036), and CXCL10 ( P = .006) and lower levels of IFN‐γ ( P = .047) in sputum at exacerbation than children with EVW. At T2, they also displayed lower plasma levels of IFN‐γ ( P = .045) and CXCL10 ( P = .013). Conclusion: Among preschool asthmatic children, MTW and SIW, prone to exacerbations, display lower systemic levels of Th1, Th2 cytokines, pro‐ and anti‐inflammatory cytokines, and antiviral responses during severe virus‐induced exacerbation.